East Asian Library Resources Group of Australia newsletter - Australian National University. Research School of Pacific and Asian Studies; Australian National University. Research School of Social Sciences; East Asian Library Resources Group of Australia; Japanese Library Resources Group of Australia (Canberra, A.C.T. : Coombs Computing Unit, Research Schools of Social Sciences & Pacific and Asian Studies, the Australian National University, 2005)
The Newsletter aims at promoting awareness of various issues in East Asian library resources and librarianship in Australia, and enhancing interaction among library professionals and individuals interested in East Asian studies.
"Incorporating the Japanese Library Resources Group of Australia."
Published by: East Asian Library Resources Group of Australia, 2012-
Title from title screen (viewed on June 22, 2005).
Text.
Mode of access: Internet via the World Wide Web. Available at: http://www.ealrga.org.au/newsletter.html
Selected for archiving
Keywords: Libraries -- Special collections -- East Asia -- Periodicals; Library science -- Australia -- Periodicals; East Asia -- Library resources -- Periodicals